AIDS and medical confidentiality. Issue 6588 (27th June 1987) - Gillon, R
Abstract : In summary, I have argued that the arguments offered or hinted at in favour of doctors' breaking medical confidentiality by passing on information about their patients' HIV state to others, including other doctors, when this is against the patient's considered wishes are generally unconvincing. Although in highly exceptional cases there may be justifications for overriding confidentiality, the requirement of medical confidentiality is a very strong, though not absolute, obligation. Patients, their contacts, doctors and their staff, and the common good are most likely to be best served if that tradition continues to be honoured.